2015
DOI: 10.1016/j.jns.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum levels of selenium, copper, and zinc are related to neuromotor impairments in children with konzo

Abstract: We assessed the relationship between key trace elements and neurocognitive and motor impairments observed in konzo, a motor neuron disease associated with cassava cyanogenic exposure in nutritionally challenged African children. Serum concentrations of iron, copper, zinc, selenium, and neurotoxic lead, mercury, manganese, cadmium, and cobalt were measured in 123 konzo children (mean age 8.53 years) and 87 non-konzo children (mean age 9.07 years) using inductively coupled plasma mass spectrometry (ICPMS). Conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 17 publications
(20 reference statements)
0
33
0
3
Order By: Relevance
“…In Africa, it has been used to study cognitive development and nutrition in Ethiopia (Bogale et al, 2013), Democratic Republic of Congo (Boivin et al, 2013; Bumoko et al, 2015) and South Africa (Taljaard et al, 2013; Rochat et al, 2016), among HIV infected children in Uganda (Boivin et al, 2010; Ruel et al, 2012; Brahmbhatt et al, 2017), and cerebral malaria in Senegal (Boivin, 2002), and Uganda (Bangirana et al, 2009). KABC-II has different sub-tests and is used in children aged 3–18 years.…”
Section: Methodsmentioning
confidence: 99%
“…In Africa, it has been used to study cognitive development and nutrition in Ethiopia (Bogale et al, 2013), Democratic Republic of Congo (Boivin et al, 2013; Bumoko et al, 2015) and South Africa (Taljaard et al, 2013; Rochat et al, 2016), among HIV infected children in Uganda (Boivin et al, 2010; Ruel et al, 2012; Brahmbhatt et al, 2017), and cerebral malaria in Senegal (Boivin, 2002), and Uganda (Bangirana et al, 2009). KABC-II has different sub-tests and is used in children aged 3–18 years.…”
Section: Methodsmentioning
confidence: 99%
“…HIV infected children and those with Konzo had lower motor scores than controls. BOT-2 scores correlated with a neurologic index score in children with Konzo (r = -0.43, p<0.0001), no other psychometric results of the BOT-2 were provided in these studies (Boivin, Okitundu, et al, 2013; Buomoko et al, 2015). …”
Section: General Comprehensive and Specific Neurodevelopment Tests (mentioning
confidence: 60%
“…The Bruininks-Oseretsky Test of Motor Proficiency (second edition) (BOT-2) (Bruininks & Bruininks, 2005) has been used to assess motor skills in HIV infected children and in children with Konzo disease in sub-Sahara Africa (Buomoko et al, 2015). HIV infected children and those with Konzo had lower motor scores than controls.…”
Section: General Comprehensive and Specific Neurodevelopment Tests (mentioning
confidence: 99%
“…Bumoko et al (2015) reported that selenium deficiency contributes to the pathogenesis of konzo through mechanisms that are responsible for oxidative damage [19].…”
Section: Tannins Contentmentioning
confidence: 99%